Pathway of Building SMEs Performance in Cluster through Innovation Capability - Faisol Faisol; Sri Aliami; M. Anas (Economics Development Analysis Journal, 2022)
The purpose of this study is to investigate the impact of business strategies and social capital on the performance of small and medium-sized firms (SMEs) that operate in small industry clusters. An emphasis is placed on examining the function of innovation capability in mediating this interaction. Data was acquired by sending questionnaires to various clusters in East Java, Indonesia, utilizing multi-stage sampling. The study then found 98 SME owners who had completed all of the surveys. The Partial Least Square approach was then utilized to evaluate the hypotheses using SmartPLS. The findings show that business strategies have no direct impact on performance. The impact of business strategy on performance appears to be mediated by innovation capabilities. On the other hand, social capital, as measured by bridging and linking social capital, has a direct impact on firm performance. As a result, this study suggests that SMEs improve their performance through increasing cluster social capital and increasing innovation capability. We recommend further research to replicate this study on large industry clusters. It is expected that the interplay between business strategies and social capital to performance will explain different result for the development of industry clusters.